2005
DOI: 10.1042/bj20050168
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ accumulation into acidic organelles mediated by Ca2+- and vacuolar H+-ATPases in human platelets

Abstract: Most physiological agonists increase cytosolic free [Ca2+]c (cytosolic free Ca2+ concentration) to regulate a variety of cellular processes. How different stimuli evoke distinct spatiotemporal Ca2+ responses remains unclear, and the presence of separate intracellular Ca2+ stores might be of great functional relevance. Ca2+ accumulation into intracellular compartments mainly depends on the activity of Ca2+- and H+-ATPases. Platelets present two separate Ca2+ stores differentiated by the distinct sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
83
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 44 publications
5
83
0
Order By: Relevance
“…CAXs identified here join SER CA3 and TMEM165 as credible candidates for filling acidic organelles with Ca 2+ (López et al, 2005;Demaegd et al, 2013). Importantly, Ca 2+ /H + transport emerges as a novel way to control cellular migration and likely other Ca 2+ -dependent events in animals.…”
Section: Cax Regulates Cell-substrate Adhesionmentioning
confidence: 99%
“…CAXs identified here join SER CA3 and TMEM165 as credible candidates for filling acidic organelles with Ca 2+ (López et al, 2005;Demaegd et al, 2013). Importantly, Ca 2+ /H + transport emerges as a novel way to control cellular migration and likely other Ca 2+ -dependent events in animals.…”
Section: Cax Regulates Cell-substrate Adhesionmentioning
confidence: 99%
“…It has long been known that Ca 2ϩ is stored in the endoplasmic reticulum (ER), which is the best-studied agonistreleasable Ca 2ϩ store; however, a number of studies have revealed that Ca 2ϩ is also dynamically accumulated in a number of acidic organelles (2), including secretory granules, lysosomes and lysosome-related organelles, endosomes, and vesicles of the Golgi complex (2)(3)(4)(5)(6). ER Ca 2ϩ store depletion has been reported to be sensed by STIM1 (stromal interaction molecule-1) (7-9).…”
mentioning
confidence: 99%
“…ER Ca 2ϩ store depletion has been reported to be sensed by STIM1 (stromal interaction molecule-1) (7-9). Although STIM1 was originally identified as a surface membrane protein in stromal cells (10) 4 The abbreviations used are: SOCE, store-operated calcium entry; ER, endoplasmic reticulum; HBS, HEPES-buffered saline; hTRPC1 and hTRPC6, human canonical TRP1 and TRP6, respectively; IP 3 , inositol 1,4,5-trisphosphate; TBHQ, 2,5-di-(tert-butyl)-1,4-hydroquinone; TG, thapsigargin; SERCA, sarco/endoplasmic reticulum Ca 2ϩ -ATPase; V-ATPase, vacuolar proton-ATPase; NAADP, nicotinic acid adenine dinucleotide phosphate; DTS, dense tubular system; AM, acetoxymethyl ester; BAPTA-AM, 1,2-bis(2-aminophenoxy)ethane-N,N,NЈ,NЈ-tetraacetic acid tetrakis(acetoxymethyl ester); GPN, glycyl-1-phenylalanine 2-naphthylamide; PDI, protein-disulfide isomerase. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sarco-endoplasmic reticulum Ca 2+ -ATPase (SERCA) inhibitor 2,5-diterbutyl benzohydroquinone (BHQ) has been shown to inhibit Ca 2+ uptake into isolated synaptic vesicles [39]. In platelets, the acidic Ca 2+ pool was controlled both by a Ca 2+ /H + exchange and by a BHQ-sensitive SERCA 3 [40,41]. Similarly, loading with Ca 2+ of dense-core insulin storage granules of mouse pancreatic ␤-cells was sensitive to both SERCA inhibitors BHQ and thapsigargin [42].…”
Section: Mechanisms Of Ca 2+ Accumulation In the Secretory Granulesmentioning
confidence: 99%